Geospatial Access to Emergency Obstetric Surgery in Indonesia: Is Travel Time for Access Too Long? - Brahmana Askandar Tjokroprawiro; Hanif Ardiansyah Sulistya; Farizal Rizky Muharram; Renata Alya Ulhaq; Alifina Izza; Budi Prasetyo; Khoirunnisa Novitasari; Budi Wiweko; Pandu Hanindito Habibie; Arya Ananda Indrajaya Lukmana; Muhammad Muhibuddin Hilmy Asari (Annals of Global Health)
Background: Ensuring timely access to safe and affordable surgery within a travel time of a 2-h drive or 30-min walk is crucial for achieving universal health coverage, as endorsed by the Lancet Commission on Global Surgery (LCoGS). In this study, we aimed to quantify the percentage of Indonesian women of reproductive age (WRA) who can access a hospital with emergency obstetric and gynecological services within this time frame. In addition, we aimed to identify the underserved populations. Methods: We identified hospitals across 38 provinces using the database from the Indonesian Society of Obstetricians and Gynecologists (ISOG) and the Indonesian Ministry of Health database that provide emergency obstetric services. We conducted geospatial analysis using the cost of distance and service area tools in ArcGIS Pro with WRA population data derived from Facebook’s high-resolution settlement layer (HRSL) maps. Results: Of the 3,202 recorded hospitals, 2,855 (89.2%) had an obstetric gynecologist (OBGYN). The workforce of 5,305 OBGYNs consisted of 4,857 (91.6%) actively practicing OBGYNs, of which 3,405 (64.2%) practice in hospitals only. Of the WRA population, 94.5% lived within 2 h of a facility. However, eight provinces had low timely access to these hospitals. Conclusion: Indonesia provides universal health coverage; however, stark disparities exist in the geographic access to emergency obstetric surgical care in certain provinces. Geospatial mapping and survey data work together to aid in assessing the strength of the surgical system and in identifying gaps in geographic access to timely surgery.